A Proximal Analytic Center Cutting Plane Algorithm for Solving Variational Inequality Problems. (30th December 2012) - Shen, Jie; Pang, Li-Ping
Abstract : Under the condition that the values of mappingF are evaluated approximately, we propose a proximal analytic center cutting plane algorithm for solving variational inequalities. It can be considered as an approximation of the earlier cutting plane method, and the conditions we impose on the corresponding mappings are more relaxed. The convergence analysis for the proposed algorithm is also given at the end of this paper.